2016
DOI: 10.1038/srep38319
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ2-induced outflow alterations in a bioengineered trabecular meshwork are offset by a rho-associated kinase inhibitor

Abstract: Members of the transforming growth factor beta (TGFβ) cytokine family have long been associated with affecting several cellular functions, including cell proliferation, differentiation and extracellular matrix (ECM) turnover. Of particular interest to this work, TGFβ2 has been linked to most types of glaucomas as a potential fibrotic agent that can cause elevation of intraocular pressure (IOP). Given that the trabecular meshwork (TM) provides most of aqueous humor outflow resistance in the eye, an in vitro bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 35 publications
5
59
0
Order By: Relevance
“…5A). Compared to rapid changes of outflow facility mediated by TGFβ2 38 , it has been reported that the effect of TGFβ1 to cause IOP elevation follows after the effect of TGFβ2 to elevate IOP 49 . This decreased permeability was attenuated by the LPA receptor antagonist, ROCK inhibitors, and TGF-β receptor inhibitor (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). Compared to rapid changes of outflow facility mediated by TGFβ2 38 , it has been reported that the effect of TGFβ1 to cause IOP elevation follows after the effect of TGFβ2 to elevate IOP 49 . This decreased permeability was attenuated by the LPA receptor antagonist, ROCK inhibitors, and TGF-β receptor inhibitor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have also shown that cytoskeletal changes induced by ECM deposition and fibrosis of HTM cells impair AH outflow through the TM, leading to IOP elevation. These changes appear to involve the Rho/ROCK pathway, which has been implicated in the control of the contractile and biomechanical properties of the TM and Schlemm's canal 38,39 . We saw a similar correlation between increased ATX and elevated IOP in our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that cytoskeletal changes correlate with increased ECM production and fibrogenic activity of HTM cells upon impairment of AH outflow following TM obstruction and IOP elevation. 49,50 Notably, these changes appear to involve the Rho/ROCK pathway, which has been implicated in the control of the contractile and biomechanical properties of cells and tissues. 49 In the present study, immunostaining revealed significant ATX expression in conventional outflow pathway specimens of glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Notably, these changes appear to involve the Rho/ROCK pathway, which has been implicated in the control of the contractile and biomechanical properties of cells and tissues. 49 In the present study, immunostaining revealed significant ATX expression in conventional outflow pathway specimens of glaucoma patients. ATX was upregulated and secreted from HTM cells following Dex treatment as demonstrated by immunofluorometry, qRT-PCR, immunoblot analysis, and two-site immunoenzymetric and lysoPLD assays.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Histological analysis indicates that the extracellular matrix (ECM) accumulates and increases resistance in the trabecular pathway. 8,9) Glaucoma is classified into two major types: open-angle glaucoma (OAG) and angle-closure glaucoma (ACG). The latter indicates an anatomically closed angle and, therefore, a surgical procedure is performed prior to medical treatment for IOP reduction.…”
Section: Introductionmentioning
confidence: 99%